Genome-wide annotation and expression analysis of WRKY and bHLH transcriptional factor families reveal their involvement under cadmium stress in tomato (Solanum lycopersicum L.) - Khan, Ibrahim; Asaf, Sajjad; Jan, Rahmatullah; Bilal, Saqib; Lubna,; Khan, Abdul Latif; Kim, Kyung-Min; Al-Harrasi, Ahmed (Frontiers in Plant Science, 2023)
The WRKY and bHLH transcription factors have been implicated in multiple physiological processes in plants, especially in plant stress responses. However, little information about the heavy metal responsive SlWRKY and SlbHLH in tomato (Solanum lycopersicum) is available. We performed a genome-wide investigation for these two TF families in S. lycopersicum and determined their role in Cadmium (Cd) stress tolerance. Furthermore, orthologs analysis with Arabidopsis genome led to classifying WRKY and bHLH orthologues genes into nine and eleven clusters, respectively. The comparative phylogenetic analysis showed gene loss and duplication events in Arabidopsis and S. lycopersicum, that occurred before and after the last common ancestor of the two species. Orthologous relationships are also supported by additional evidence, such as gene structure, motifs compositions, and protein-protein interaction networks of most genes, suggesting their similar functions. Comprehensive transcriptomics analysis revealed that both WRKY and bHLH genes were differentially expressed in response to cadmium stress as compared to control plants. A gene ontology analysis indicated that most of WRKYs and bHLHs proteins are involved in DNA binding activities and gene expression regulation. Analyses of interaction networks suggested that both WRKYs and bHLHs mediate networks involved in multiple stress-signalling pathways. The findings of this study may help clarify the intricate transcriptional control of bHLH genes and identify putative stress-responsive genes relevant to the genetic improvement of tomato. Moreover, identifying heavy metal stress-responsive WRKY and bHLH genes in S. lycopersicum will provide fundamental insights for developing new heavy metal stress-tolerant varieties of tomato crops.